Studying the Existence of Progressive Law in Handling Children Faced with the Law (Activa Yuris: Jurnal Hukum, 2022)
Children are special legal subjects, judging from the legal responsibilities they have. The legal conception places children as legal subjects that are different from adults, both in the civil realm and in the realm of criminal law. Progressive law, as well as placing children as legal subjects that are special in nature, that is, they are included in "those who are vulnerable" and need special protection and treatment. This article will discuss the different treatment of children, who are in conflict with the law, not as a form of discrimination but as a form of special treatment for special legal subjects. The writing of this article uses a normative legal research method with a conceptual approach and legislation. The results of this research are that children as a vulnerable group need to get special attention and special treatment to support the process of growth and development as the nation's next generation